COVID-19: Challenges and solutions for the provision of care to seriously ill and dying people and their relatives during SARS-CoV-2 pandemic – perspectives of pandemic response team members: A qualitative study on the basis of expert interviews (part of PallPan). (July 2022) - Klinger, Isabell; Heckel, Maria; Shahda, Sophie; Kriesen, Ursula; Schneider, Carolin; Kurkowski, Sandra; Junghanss, Christian; Ostgathe, Christoph
Background: During the SARS-CoV-2 pandemic's initial waves, bans on visiting and isolation measures placed limits on providing services for seriously ill and dying people and their relatives. Pandemic response teams at governmental level (macro), at federal state and municipal level (meso) and in healthcare facilities (micro) played their role in pandemic management procedures. Aim: To explore pandemic-related challenges and solutions of pandemic response teams regarding the provision of care to seriously ill and dying people and their relatives. Findings were to be integrated into a national strategy (PallPan). Design: Semi-structured expert interviews (10/2020–2/2021) analysed via structured content analysis. Setting/ Participants: We interviewed 41 members, who discussed the work of 43 German pandemic response teams (micro n = 23; meso n = 20; no members were available at macro level) from 14 German federal states. Results: Twenty-nine of 43 teams took account of the needs of seriously ill and dying. Their main challenges resulted from pandemic-related legal requirements in hospitals and long-term care facilities. The implementation of such was in the remits of the meso level. Dysfunctional or non-existent communication between the levels was reported to be challenging. To foster patient-related solutions the micro level pandemic response teams supported individual decisions to enable patient-relative contact for example, visiting and saying goodbye outside, meeting via digital solutions. Conclusions: Pandemic response teams evidently struggled to find appropriate solutions to ease pandemic-related impact on the care of seriously ill and dying patients and their relatives. We recommend bringing palliative care expertise on board.